Costs and benefits of electricity subsidies in Uganda - Byaruhanga, Charles Victor (Research of GSB, 2018)
Electricity subsidies in Uganda have been pervasive in support of industrial output and government revenues since 2005, until their reduction in January 2012. While economic theory suggests that market mechanisms maximise social welfare, the necessity for subsidies arises when a markets fail. However, market failure alone is not a sufficient condition to provide subsidies, as they are costly, and therefore have to be properly targeted and justified. This research seeks to establish the relationship between electricity subsidies, on the one hand and industrial output and government revenues in Uganda. It also attempts to ascertain the equitability of the electricity subsidy policy. Information and data was gathered from secondary sources in Uganda on electricity subsidies, industrial output and revenues during the period 2005 to 2012. For an empirical investigation of the costs and benefits of electricity subsidies in Uganda, certain logical relationships are identified in the study to guide the empirical investigation and the analyses. It is assumed that government revenues were dependent on electricity subsidies and industrial output during the period under investigation, in order to maintain social welfare. It was also argued that the maintenance of industrial output through electricity subsidies support was justified given that about one third of Uganda total revenues are contributed by the manufacturing sub-sector. To ascertain the extent of vertical equity, the research also investigated the benefit incident of electricity subsides, from a macro-level standpoint. This is pertinent given that only 11 per cent of Ugandans have access to grid-power and electricity use favours higher income, urban end-users. Secondary data on excise and corporate tax collections and electricity subsidies provided to end-users in Uganda during period are statistically analysed for relational effects using Ordinary Least Square regression models. The respective estimators in the relationship reveal very strong relationships between excise and corporate tax revenues, on the one hand, and electricity subsidies. Electricity subsidies were found to be positively related to both excise and corporate tax revenues and industrial output during the period under study. From the evidence, the overall objective of the electricity subsidy policy seems to have been attained, in as far as revenues base was protected and industrial output was maintained. The evidence also reveals that at a macro-level, end-user beneficiaries of subsidies in the manufacturing sub-sector continued to make profits, enabling them meet their corporate tax obligations.